P209 Delayed IBD diagnosis increases risk of requiring biologics in first 4-years - an Inception cohort study. (30th January 2023) - Rao, A; Bazarova, A; Mitra, P; Parigi, T; Majumder, S; Ghosh, S; Iacucci, M; Shivaji, U
Abstract: Background: Delays in diagnosis can be due to patient and health-system related factors. The impact of such delays in Inflammatory Bowel Diseases (IBD), particularly on biological therapies, continues to be of interest. The aim of the study was to investigate if delays could predict need for biologics and report on related adverse outcomes (AOs). Methods: New patients referred for suspected IBD to a single tertiary care centre between Jan 2013 to Dec 2017 were identified using EMR. For this study, delay-types and cut-off times for each type were set based on best average hospital waiting times. The reasons for delays until start of treatment were recorded; data on the start of biologics, duration, and reasons for switch (if required) were recorded. Data was analysed using multiple Pearson correlations and Cox proportional Hazard model to determine whether any delay-types could predict need for biologics and compare the risk between patients with or without delay. Results: 105 patients were identified using stringent criteria (M=58; median age=32y) with a median follow-up of 55 months. 65, 27 and 13 patients had a final diagnosis of Ulcerative colitis, Crohn's disease, and Unclassified colitis respectively, and were analysed collectively. A model that combined delay in seeking medical attention, and time taken from specialty review to index endoscopy exhibited the best predictive power with average AUROC of 0.67. When individual delay-types were analysed, it was noted that most delay-types increased the risk of biologic use: a) delay in seeking medical attention [OR-1.08(1.03 1.17)] b) delay from GP referral to specialty review [OR-1.10(1.0 1.23)] c) delay from specialty review to index endoscopy [OR-1.09(1.01 1.21)] On further analysis, there was a statistically significant increase noted in the risk of requiring biologics at any time during the follow-up period. Fig 1A illustrates survival without biologics when there is a delay of >2 weeks in seeking medical attention (p=0.042 ). Figure 1B illustrates survival without biologics when there is delay of >6 weeks from GP referral to index endoscopy (p=0.021 ). Figure 1A- Patient-related delay of >2weeks and risk of needing biologics (p=0.042) Figure 1B- Health-system related delay of >6weeks and risk of needing biologics (p=0.021) Conclusion: The risk of requiring biologic therapy is higher in those patients who have faced any type of delay in their diagnosis of IBD. A patient-related delay of >2weeks and cumulative health-system related delay of >6weeks increase the risk of requiring biologic therapy at any time during their follow-up. Both primary and secondary care must work to reduce any delays as this has long-term implications for patients and economic implications for health care providers.